PERANAN SANDO MPOANA DI KECAMATAN SIRENJA KABUPATEN DONGGGALA - Andi Mascunra Amir; Abdul Kadir Patta; Zaiful; Moh. Azan Arrahman (Kinesik, 2023)
This study aims to know how is The Role of Sando Mpoana (traditional birth midwives) in Sirenja subdistrict Donggala Regency in the community especially in Sirenja subdistrict Donggala Regency. The study outcomes showed that Sando Mpoana have a significant position in the social structure - but over time this position has extremely decreased due to the existence of the government regulation in terms of childbirth must be carried out at he nearest health care facility or local health center. It was a fact that the role of Sando Mpoana is very helpful in assisting childbirth, especially in rural communities, coupled with reluctant of mothers to give birth to medical personnel, both modern midwives and practicing doctors, Not only that, in certain conditions, for example when a mother is experiencing childbirth, traditionel midwives personnels are needed to bathe and massage the baby, Based on these circumstances, the local health office coorporates and increases the capacity of Sando Mpoana in order to reduce illness risks. Childbirth in Sirenja subdistrict under normal conditions, the traditional midwives are obliged to carry out childbirth at the Sirenja Health Center, but in certain condition the traditional baby midwives can do it independently but still have to be accompanied by modern midwives personnels to help cut baby’s placenta and to record births.